2015
DOI: 10.1016/j.adolescence.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of best friends in educational identity formation in adolescence

Abstract: This 4-year longitudinal study examined over-time associations between adolescents' educational identity, perceived best friends' balanced relatedness, and best friends' educational identity. Adolescents (N = 464, Mage = 14.0 years at baseline, 56.0% males, living in the Netherlands) and their self-nominated best friends reported on their educational commitment, in-depth exploration, and reconsideration. Target adolescents also reported on the level of balanced relatedness provided by their best friend. Cross-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(53 reference statements)
0
15
0
1
Order By: Relevance
“…The development of a stable set of commitments to choices in various areas of life, such as friendships and education is considered a central developmental task of adolescence (Erikson, 1950). In accordance with the importance of identity, previous studies have consistently linked strong commitments to positive adolescent adjustment (Berzonsky, 2003;Luyckx et al, 2007;Van Doeselaar et al, 2016) and adolescent well-being (e.g., Meeus, 2011;Sandhu et al, 2012). For example, adolescents in the identity clusters achievement and foreclosure reported higher well-being than adolescents in moratorium or diffusion (Luyckx et al, 2005).…”
mentioning
confidence: 75%
“…The development of a stable set of commitments to choices in various areas of life, such as friendships and education is considered a central developmental task of adolescence (Erikson, 1950). In accordance with the importance of identity, previous studies have consistently linked strong commitments to positive adolescent adjustment (Berzonsky, 2003;Luyckx et al, 2007;Van Doeselaar et al, 2016) and adolescent well-being (e.g., Meeus, 2011;Sandhu et al, 2012). For example, adolescents in the identity clusters achievement and foreclosure reported higher well-being than adolescents in moratorium or diffusion (Luyckx et al, 2005).…”
mentioning
confidence: 75%
“…This sense of personal continuity is one of the key aspects of Erikson's conceptualization of an adaptive identity, which is still present in the narrative (McAdams 2001) and dual-cycle approaches (Van Doeselaar et al 2018). Moreover, both approaches also still recognize the importance of social (e.g., McLean and Jennings 2012;Van Doeselaar et al 2016) and cultural (e.g., McLean and Syed 2015;Negru-Subtirica et al 2017) contexts for identity formation. Yet, in both approaches distinct, but complementary, theoretical ideas on the conceptualization of an (adaptive) personal identity and how a personal identity is constructed and maintained have been added to those of Erikson.…”
Section: Erikson's Views On Identity Formationmentioning
confidence: 99%
“…While the participating adolescents considered their teachers', parents', and friends' ideas of what they should do in their future careers to be largely unlikely, these external ideas nevertheless influenced their emotional experience, although this influence was not necessarily decisive. Prior research had, for example, already shown that adolescents do only slightly adapt their educational and career aspirations to those of their friends [56].…”
Section: Discussionmentioning
confidence: 99%